Smoking modifies pancreatic cancer risk loci on 2q21.3 - Mocci, Evelina; Kundu, Prosenjit; Wheeler, William; Arslan, Alan A.; Beane-Freeman, Laura E.; Bracci, Paige M.; Brennan, Paul; Canzian, Federico; Du, Mengmeng; Gallinger, Steven; Stolzenberg-Solomon, Rachael (Cancer research, 2021)
Germline variation and smoking are independently associated with pancreatic ductal adenocarcinoma (PDAC). We conducted genome-wide smoking interaction analysis of PDAC using genotype data from four previous genome-wide association studies in individuals of European ancestry (7,937 cases and 11,774 controls).